A rare cause of culture negative bioprosthetic valve endocarditis: a case report of Aggregatibacter aphrophilus infection. Issue 2 (8th February 2021) - Wassef, Nancy; Sarkar, David; Viswanathan, Girish; Hughes, Gareth Morgan; Salisbury, Thomas; Kuo, James; de Silva, Ravi
Abstract: Background: The prevalence of culture negative infective endocarditis (IEC) is reported as 2–7% though this figure may be as high as 70% in developing countries. 1 This higher rate will, at least in part, be due to reduced diagnostic facilities though some data suggests higher rates even when appropriate cultures were taken. The frequency is significantly elevated in patients who have already been exposed to antibiotics prior to blood cultures. 1, 2 A rare cause of culture negative IEC is the HACEK group of organisms that are normal habitants of the oropharyngeal flora and account for 1–3% of native valve endocarditis. 3 Aggregatibacter aphrophilus (A. aphrophilus) is a member of the HACEK group of organisms. Case summary: A 32-year-old gentleman with a previous bioprosthetic aortic valve presented with a 1-week history of diarrhoea, vomiting, malaise, and weight loss. He was awaiting redo surgery for stenosis of the bioprosthesis, which had been inserted aged 17 for aortic stenosis secondary to a bicuspid valve. The initial blood tests revealed liver and renal impairment with anaemia. A transoesophageal echocardiogram demonstrated a complex cavitating aortic root abscess, complicated by perforation into the right ventricle. He underwent emergency redo surgery requiring debridement of the aortic abscess, insertion of a mechanical aortic prosthesis (St Jude Medical, USA), annular reconstruction and graft replacement of the ascending aorta. Despite antibiotic therapy, he remained septic with negative blood and tissue cultures. Bacterial 16S rRNA gene sequencing confirmed A. aphrophilus infection, for which intravenous ceftriaxone was initiated. This was subsequently changed to ciprofloxacin due to neutropenia. The patient self-discharged from the hospital during the third week of antibiotic therapy. One week later, he was re-admitted with fever, night sweats, and dyspnoea. Transthoracic echocardiogram revealed a large recurrent aortic abscess cavity around the aortic annulus fistulating into the right heart chambers; this was confirmed by a computed tomography scan. There was dehiscence of the patch repair. Emergency redo aortic root replacement (25 mm mechanical valve conduit, ATS Medical, USA) and annular reconstruction was performed with venoarterial extracorporeal membrane oxygenation (VA-ECMO) support. VA-ECMO was weaned after 3 days. The patient completed a full course of intravenous meropenem and ciprofloxacin and made a good recovery. Discussion: IEC with oropharyngeal HACEK organisms is rare and difficult to diagnose, due to negative blood culture results. The broad-range polymerase chain reaction and gene sequencing with comparison to the DNA database is useful in these circumstances. This case demonstrates the importance of the 16S rRNA gene sequencing for HACEK infection diagnosis and appropriate antibiotic treatment.